2004
DOI: 10.1093/ndt/gfh306
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of haemodynamic instability and heart rate variability during haemodialysis

Abstract: These data suggest that haemodynamic instability is strongly associated with a decreased HRV and an impaired sympathovagal balance, suggesting disturbed autonomic control in uraemic patients with cardiac damage. Patients with ischaemic heart disease, reduced left ventricular systolic function and decreased HRV may be at the highest risk to be haemodynamically unstable during haemodialysis. The role of early detection and treatment of ischaemic heart disease in preventing symptomatic hypotensive episodes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
82
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 15 publications
11
82
2
2
Order By: Relevance
“…Our results suggest that a low value of LF/HF of HRV may indicate a decreased capacity for activating sympathetically mediated HR and vasoconstriction mechanisms in response to hypotension, thus predisposing to the development of PRS following reperfusion. These results are in agreement with the result of previous studies showing that hypotension episodes during hemodialysis are significantly associated with decreased LF/HF [13,31]. Although altered cardiovascular autonomic control may not provide the entire explanation for the occurrence of graft reperfusion-related hypotension during liver transplantation surgery, the evaluation of HRV indices, including LF/HF appears to be particularly helpful in predicting PRS occurrence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results suggest that a low value of LF/HF of HRV may indicate a decreased capacity for activating sympathetically mediated HR and vasoconstriction mechanisms in response to hypotension, thus predisposing to the development of PRS following reperfusion. These results are in agreement with the result of previous studies showing that hypotension episodes during hemodialysis are significantly associated with decreased LF/HF [13,31]. Although altered cardiovascular autonomic control may not provide the entire explanation for the occurrence of graft reperfusion-related hypotension during liver transplantation surgery, the evaluation of HRV indices, including LF/HF appears to be particularly helpful in predicting PRS occurrence.…”
Section: Discussionsupporting
confidence: 91%
“…These observations suggest that there is a relationship between cardiovascular autonomic control and hemodynamic stability during liver transplantation surgery. Furthermore, cardiovascular autonomic indices derived from power spectral analysis, such as the ratio of low frequency power to high frequency power (LF/HF) or the total power of heart rate variability (HRV), have attracted attention with regard to their potential use in predicting hypotensive episodes in patients undergoing anesthesia or hemodialysis [13][14][15]. However, the association between cardiovascular autonomic indices and reperfusion-related hemodynamic instability during liver transplantation remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Because 24-hour SDNN is substantially contributed by the day-night difference in heart rate (6), it could be influenced by hemodialysis session. In addition, SDNN is known to decrease with hemodialysis itself, particularly when the hemodialysis involves hemodynamic instability (25).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given that CMRI was used to determine our cohort's LVM, it is reasonable to assume that our assessment of LVM was less likely to be confounded by various measurement errors such as excess extracellular fluid volume, a problem known to plague echocardiogram-derived estimates of LVM. Studies of HRV and ESRD have consistently shown a decrement in HRV (2,20,21). Reduced HRV has been established as an independent risk factor in patients with high cardiac risk profile (22), which was exemplified by The Autonomic Tone and Reflexes After Myocardial Infarction (3) trial.…”
Section: Discussionmentioning
confidence: 99%